Desarrollo de un módulo de entrenamiento para el estudio de sistemas de control, empleando hardware y software libre, para los laboratorios de la carrera de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi. - Juan Carlos, Capa Cando (2020)
The analysis and experimentation of Control Systems applied to different processes is one of the important aspects that must be consider in the academic training ofthe moment of visualizing each of its variables with its own controls and even more so that technology advances by leaps and bounds. That is why the present technological proposal aims to develop a training module for the study of Control Systems using free-use hardware and software, to be carried out in the laboratory of the Electromechanical Engineering Degree of the Technical University of Cotopaxi. The device has implemented processes of temperature, light intensity, speed and position in order to be able to experiment in each of these variables the development of controllers and tuning methods. The use of free software as a data acquisition card, added to it, MyOpenLab as a free design platform for virtual instrumentation, allows real-time analysis of the processes, where the control logic is performed to stabilize each of the processes and the experimentation of tuning methods. One of the potentialities of the module is that it allows the connection with different controllers that can range from microcontrollers to PLCs regardless of the model and brand, thereby allowing the implementation of classic controls such as ON-OFF and PID control.